Pengaruh Faktor Situasional Dan Store Atmosphere Terhadap Pembelian Impulsif Dengan Motivasi Belanja Hedonik Sebagai Intervening - makal, Eirene Natalia (Universitas Sam Ratulangi, 2018)
Impulsive buying is a spontaneous and unplanned, emotionally stimulated buying behavior, where the buying decision made immediately without thinking wisely, having any consideration and ignoring overall information and alternatives. The aim of this research is to analyze the effect of situational factors and store atmosphere on impulsive buying of housewives in Hypermart Manado Town Square through hedonic shopping motivation as intervening variable. The research showed that situational factor does not have significant effect on hedonic shopping motivation. Store atmosphere have a positive and significant effect on hedonic shopping motivation. Situational factor have positive and significant effect on impulsive buying. Store atmosphere does not have significant effect on impulsive buying and hedonic shopping motivation have positive and significant effect on impulsive buying of housewives in Hypermart Manado Town Square. Keywords: situational factor, store atmosphere, hedonic shopping motivation,impulsive buying